Improved Reduction of the Tibiofibular Syndesmosis with Tightrope Compared to Screw Fixation: Results of a Randomized Controlled Study. Issue 3 (14th September 2018) - Taylor, Michel; Sanders, David; Tieszer, Christina
Category: Trauma Introduction/Purpose: Flexible fixation of the tibio-fibular syndesmosis is designed to allow increased ankle motion and to potentially improve clinical outcomes compared to screw fixation. Flexible fixation has also been suggested to improve the rate of anatomic reduction. This randomized, multi-center study was designed to compare the rate of malreduction following treatment of high fibular fractures associated with syndesmosis injury with open reduction and internal fixation with either two fully threaded screws or one knotless Tightrope device. Methods: 101 patients from eleven sites were randomized and underwent operative fixation of their AO/OTA 44-C injury between June 2015-16. All patients demonstrated radiographic syndesmosis diastasis or instability following malleolar bony fixation. Open syndesmosis reduction was performed in all cases. Fixation was randomized to either Tightrope (T) or screws (S). Surgical techniques and rehabilitation were standardized. Follow-up at 2 and 6 weeks, 3, 6 and 12 months. The primary outcome measure was the rate of malreduction based on bilateral ankle CT scan results at 3 months post fixation. Secondary outcome measures included adverse events, reoperation, and validated functional outcomes including the EQ5D, OM Score, FADI, and WPAI. The estimated sample size required to detect a difference in reduction rate was 72 patients, but the estimated sample size required to detect a difference in functional outcome scores was 240 patients, suggesting the study was adequately powered for radiographic results only. Results: The rate of malreduction was 39% using screws compared to 15% using Tightrope (p = 0.028). Analysis of CT results was performed using a 2 mm translation or 10 degree rotation threshold for malreduction, and included fibular translation, syndesmosis distance, medial compression; and rotation. Patients in Group T had greater anterior translation compared to the contralateral limb (p=0.007) or Group S (p = 0.04). Group T syndesmoses also had greater diastasis compared to control limb (p=.005) and less fibular medialization compared to Group S (p = 0.05). Functional outcome measures demonstrated significant improvements but no differences between groups. FADI scores at each time interval were equivalent. The reoperation rate was higher in the screw group compared to Tightrope (30% vs 4%, p= 0.02). Conclusion: Treatment of tibio-fibular syndesmosis injury with the knotless flexible Tightrope device achieves lower rates of malreduction and reoperation compared to screw fixation.